Moderatisme Kader Milenial NU: Analisis Penerapan Nilai-Nilai Pendidikan Islam Moderat di LP MA’ARIF NU Babat: Penelitian - Zahrotun Nisa; Saeful Anam (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to analyze the understanding and implementation of moderate Islamic education values among millennial cadres of Nahdlatul Ulama at LP Ma’arif NU Babat. Using a descriptive qualitative method with a case study approach, data were collected through observation, interviews, and documentation. The data were then analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The findings reveal that the cadres' understanding of moderate Islam developed progressively through four constructivist stages: schema, assimilation, accommodation, and social interaction. Initially, their perception was limited, viewing Islamic moderation mainly as tolerance toward other religions. However, after participating in structured educational and organizational activities, they began to internalize and practice core moderate values such as tawassuth (moderation), tawazzun (balance), tasammuh (tolerance), i’tidal (justice), and syura (deliberation). These values are embedded in their attitudes, decision-making processes, and social interactions. The study concludes that consistent and value-based education, supported by teacher modeling and institutional culture, significantly shapes young NU cadres to become inclusive, tolerant, and socially responsible Muslim leaders in modern society.